La défense Lincoln Roman - Connelly, Michael 1956- (Points, 2006)
Representing the system's most unsavory characters in his work as a criminal defense lawyer, jaded attorney Mickey Haller takes on his first high-paying and possibly innocent client in years, but finds the case complicated by sinister events that suggest the workings of a particularly evil perpetrator.